Border Control and the Degradation of Labour - Bosworth, Mary (The British journal of criminology, 2024)
This article uses testimonies from private sector staff about their experiences of working in sites of short-term immigration detention and in facilitating deportation, to explore the material conditions of this form of custodial labour. Until now, most criminological accounts of criminal justice or border staff have paid little attention to them as workers. As a result, the connections between sites and practices of custody and capital have been obscured. Drawing on a range of scholarship about the labour market and the nature of work, the piece concludes by advocating for new alliances to challenge the precarity and poverty that both lead people into these jobs and justifies them and the exclusionary and divisive politics they engender.